Coronary artery disease prediction in men: Use of apolipoproteins A-1 and B - (:unkn) unknown (My University, 2005)
This case-control study was conducted to determine the predictors of coronary artery disease (CAD) and to evaluate the predictivity of the relatively new parameters of apolipoprotein A-I (apo A-I) and apolipoprotein B (apo B) in Turkish male subjects. Cases (n=131) were subjects with CAD, while controls (n=103) were those without CAD determined on angiography. In a fully adjusted model, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and TC/HDL-C were found to be the independent lipid-related predictors of CAD in Turkish men, while the relatively new parameters of apo A-I and apo B were not found to be predictive. It can be suggested that for CAD prediction in men, routine measurements of apo A-I and apo B for screening purposes are not as necessary as the traditional lipid parameters.
Keywords: Angiography; Apolipoprotein A-I; Apolipoprotein B; Coronary artery disease; Men; Predictive; Risk factors